Sociology of Tourism: Shifting Paradigm from Nostalgia to Happiness - Sharma, Ramji (Journal of Tourism and Hospitality Education, 2020)
Travel is not a recent genre. However, the concept of modern tourism is a naïve charm. Due to its outrageous rumble worldwide, it has now become the biggest industry of 21st century. With the growth, tourism has gradually been creating its own space in academia. Sociologists also could not remain oblivious to tourism’s multifaceted implications on individual, society and culture. Boorstin endeavored to pull tourism in sociological domain since 1962 but could create its own niche in Sociology in 70s specifically with the advent of prominent scholars like Dean MacCannell and John Urry in this premise. Tourism now has become an appealing proposition in sociology though it’s theoretical gravity and methodological progression is still in embryonic stage. Th e objective of this paper is to review and synthesize the cognition of tourism in sociological domain from escapism (nostalgia) disposition to the current trend of happiness premise.